Albizia Falcataria (Paraserianthes Falcataria) A Newly Emerging Export Earner in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT Since 1980, the wood industry in Indonesia has grown at a rapid rate. Whithin the course of 10 years a substantial number of sawmills and plywood mills were set up. Related industries that have also been established include blockboard, particle board, pulp and paper and rayon. Together, these industries are utilizing wood from the tropical rain forests at a rate of about 20 million m3 a year. There are indications that wood industries will continue to grow, the latest major trend being toward the production of pulp and paper. By the year 2000 it has been estimated that the demand for wood will be araound 90 million m3 and the existing tropical rainforests would definitely be unable to meet the demand. In response to this situation, Indonesia has embarked on a massive forest plantation program which is projected to cover a total area of 6.2 million hectares within the next 15 to 20 years. Twenty different free species have been recommended by the Ministry of Forestry for the development of these plantations. One of these species, Albizia fakataria (or Paraserianthes falcararia) is discussed in this paper with regard to its nomenclature